2020
DOI: 10.1186/s40795-020-00332-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of stunting among children aged 6 to 59 months in pastoral community, Afar region, North East Ethiopia: unmatched case control study

Abstract: Background: Stunting is defined as a child with a height for-age Z-score less than minus two standard deviations. Globally, 162 million less than 5 years were stunted. In Ethiopia, Nationally the prevalence of stunting among under five children was 38.4% and in Afar it is above the national average (41.1%). This study was aimed to identify determinants of stunting among children aged 6 to 59 months in rural Dubti district, Afar region, North East Ethiopia, 2017. Methods: Community based unmatched case-control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
34
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 19 publications
14
34
0
11
Order By: Relevance
“…Mothers with better education levels are also presumed to have a better understanding of choosing better or risky behaviors (26,27), both for their health and for the health of their children. This finding confirms the results of several previous studies in various countries which inform that poor education mothers increase the risk of children under five to be stunted (18,28,29). In line with these findings, a study in North East Ethiopia reported that toddlers who have no education mother are 4.92 times more likely to be stunted (28).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Mothers with better education levels are also presumed to have a better understanding of choosing better or risky behaviors (26,27), both for their health and for the health of their children. This finding confirms the results of several previous studies in various countries which inform that poor education mothers increase the risk of children under five to be stunted (18,28,29). In line with these findings, a study in North East Ethiopia reported that toddlers who have no education mother are 4.92 times more likely to be stunted (28).…”
Section: Discussionsupporting
confidence: 90%
“…This finding confirms the results of several previous studies in various countries which inform that poor education mothers increase the risk of children under five to be stunted (18,28,29). In line with these findings, a study in North East Ethiopia reported that toddlers who have no education mother are 4.92 times more likely to be stunted (28).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Stunting is one of the most important public health problems in Ethiopia with a double burden of undernutrition comprising both wasted and stunted under-five children. Most studies indicated that stunting is associated with low socioeconomic status, low educational level of parents, poor water supply and sanitation, and high infectious disease burden [12][13][14]. e basic and major food source for the study area was "Enset," and there was high population density and polygamous marriage was common in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…These can broadly be classified into basic factors like child characteristics (Woldeamanuel and Tesfaye 2019), parental characteristics (Kahssay et al 2020), and household characteristics (Woldeamanuel and Tesfaye 2019). Moreover, underlying factors like food insecurity (Mulu and Mengistie 2017) and sanitation (Girma et al 2019;Kahssay et al 2020;Woldeamanuel and Tesfaye 2019) and immediate factors such as inadequate dietary intake (Girma et al 2019) and infections (Mulu and Mengistie 2017;Woldeamanuel and Tesfaye 2019) were associated with child wasting and stunting. However, there is a lack of information about risk factors of child wasting and stunting evaluated through cohort study in drought-prone areas of Sidama.…”
Section: Introductionmentioning
confidence: 99%